(untitled) (Iranian Journal of Kidney Diseases, 2020)
Coronaviruses primarily cause zoonotic infections, however in the past few decades several interspecies transmissions have occurred, the last one by SARS-CoV-2, causing COVID-19 pandemic, posing serious threat to global health. The SARS-CoV-2 spike (S) protein plays an important role in viral attachment, fusion and entry. However, other structural and non-structural SARS-CoV-2 proteins are potential influencers in virus pathogenicity. Among these proteins; Orf3, Orf8, and Orf10 show the least homology to SARSCoV proteins and therefore should be further studied for their abilities to modulate antiviral and inflammatory responses. Here, we discuss how SARS-COV-2 interacts with our immune system.